2021
DOI: 10.3389/fneur.2021.728984
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling Reveals the Antiapoptosis and Antioxidant Stress Effects of Fos in Ischemic Stroke

Abstract: Arterial hypertension is considered the most prevalent risk factor for stroke. Both pathophysiologic and clinical data previously acquired suggest a strong correlation between the hemodynamic nature of arterial hypertension and an increase in the risk of ischemic insult to tissues. However, the knowledge of specific molecular interactions between hypertension and ischemic stroke (IS) is limited. In this study, we performed systematic bioinformatics analysis of stroke-prone spontaneous hypertensive brain tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Interestingly, the fifth cluster also mainly involves the interleukin signaling pathway, and the interaction of FOS and CCL2 genes in this cluster may play a bridging role. FOS is a potential target gene for Crohn's disease (CD) 69 , where downregulation of FOS significantly enhances oxidative stress levels, accelerates neuronal apoptosis, and inhibits mitochondrial function, increasing the risk of ischemic stroke 70 . CCL2 is intimately associated with unstable atherosclerosis as upregulated based on inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the fifth cluster also mainly involves the interleukin signaling pathway, and the interaction of FOS and CCL2 genes in this cluster may play a bridging role. FOS is a potential target gene for Crohn's disease (CD) 69 , where downregulation of FOS significantly enhances oxidative stress levels, accelerates neuronal apoptosis, and inhibits mitochondrial function, increasing the risk of ischemic stroke 70 . CCL2 is intimately associated with unstable atherosclerosis as upregulated based on inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Mu et al confirmed that FOS has a strong correlation with the occurrence and prognosis of infantile spasm; moreover, lentivirusmediated FOS knock-down significantly increased the oxidative stress level, neuronal apoptosis and inhibited mitochondrial function (p < 0.05). 16 The AP-1/c-FOS cytokine-signalling axis can modulate recombinant TNFα leading to a strong upregulation of IL-6 mRNA expression and protein secretion, thereby promoting vascular calcification. 17 In this study, our goal was to identify novel genetic factors involved in VTE pathogenesis to facilitate its early diagnosis.…”
Section: Introductionmentioning
confidence: 99%